The relationships between job performance, job burnout, and psychological counselling: a perspective on sustainable development goals (SDGs) - Lei, Miao; Alam, Gazi Mahabubul; Bashir, Karima (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Job burnout (as an independent variable) and job performance (as a dependent variable) are often correlated, and one of the main arguments is that psychological counseling can mitigate job burnout, which in turn influences job performance. This article aims to introduce a new perspective on the subject by establishing a new paradigm in the field. It also explores the role of psychological counseling as a precautionary measure. Furthermore, it aligns with the United Nations Sustainable Development Goals (SDGs) 3 and 8, which seek to enhance public health, collective well-being, and decent work or at least equitable workplace conditions. Adopting a quantitative analysis method, this study used panel data from 2020 to 2023 and group regression to analyze these data. The instruments comprise job performance (KPI) and mental health records. This study revealed that job burnout as experienced by academics is regulated by their job performance (β = −0.013, p < 0.001. This study revealed that academics’ job performance remained unchanged despite the number of psychological counseling and interventions conducted, so consequently, psychological counseling and interventions do not affect performance directly. This research contributes to the literature by utilizing a novel measurement approach. It is concluded that competency is the key to having a decent work environment and staff experiencing collective well-being.